Graphical interactive user interface system for a stationary trainer to perform lower limb rehabilitation tasks. Issue 1 (January 2021) - Mohan, Santhakumar; Sunilkumar, Parvathi; Khawase, Chaitanya; Rybak, Larisa
Abstract: The graphical interactive user interface system of a stationary trainer for performing lower-limb rehabilitation tasks is presented in this article. The stationary trainer considered here for the interactive system development is based on a foot-plate operating system. The foot-plate is an end-effector of a parallel Cartesian manipulator. The interactive system primarily designed for the therapeutic tasks associated with passive range of motion (PROM) of the lower limbs. Further, the interactive system concentrated on the hip and knee joint motion therapies which include flexion/extension of knee and hip as well as abduction/adduction of hip. Various clinically suggested motions along with their working nature are designed in the interactive user interface. The suggested interface would generate the system settings (the various system parameters to be fixed during the real-time training) are generated based on the patient's physical parameters such as limb length, patient's weight, height, etc. The interactive simulator of the stationary trainer is demonstrated and verified using computer-based numerical simulations.